Healthcare behaviour during a health crisis: the case of COVID-19 in Madagascar - Marilys Victoire Razakamanana; Miora Rakotonirainy; Tiarinisaina Olivier Ramiandrisoa (Springer, 2024)
Abstract A health crisis can affect the attitude towards healthcare seeking of the population. During the COVID-19 pandemic, two situations arose: people either sought care out of caution and vigilance, or because of the fear of contracting the virus and the health restrictions, they did not consult the healthcare facilities. This paper aims to analyze the effects of a health crisis such as COVID-19 on the use of healthcare in Madagascar. Two diseases, diarrhoea and fever, are considered. Fever is a common symptom of COVID-19, and diarrhoea is one of the causes of morbidity in Madagascar and a less common symptom of the pandemic. Data from the Multiple Indicator Cluster Survey in 2018 and the Rapid Survey on the Socio-Economic Impact of COVID-19 in Madagascar in 2020 are used. Considering the same individuals surveyed in 2018 and 2020, after verification of the endogeneity, the absence of it is raised. Probit models without instrumental variables are used. During the pandemic, in the case of diarrhoea, faced with the fear of a pandemic, people have sought other alternatives, such as Community Health Workers (CHWs), which is considered less risky than health centres (0.33; p-value = 0.05). In the case of fever, people out of caution, prefer to consult health centres rather than self-medicate (− 1.86; p-value = 0.00). People's behaviour differs according to the symptoms of their illness, diarrhoea being less well-known and less frequent as a symptom of COVID-19 than fever.